2011
DOI: 10.1016/j.jdent.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of natural antimicrobials in toothpaste formulations against oral biofilms in vitro

Abstract: Supernatants based on herbal- and chitosan-based toothpastes have comparable immediate and ongoing antibacterial efficacies as chlorhexidine. Natural antimicrobials and chlorhexidine absorb in oral biofilms which contributes to their substantive action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 26 publications
1
48
0
5
Order By: Relevance
“…Dentifrices containing plant extracts have been investigated and administered for a number of years in different countries (1,21). Although previous studies have already addressed the antimicrobial activity of rosemary on S. mutans, creation of a toothpaste with a defined therapeutic dose of rosemary (as the only antimicrobial agent in the formula) is a novelty.…”
Section: Discussionmentioning
confidence: 99%
“…Dentifrices containing plant extracts have been investigated and administered for a number of years in different countries (1,21). Although previous studies have already addressed the antimicrobial activity of rosemary on S. mutans, creation of a toothpaste with a defined therapeutic dose of rosemary (as the only antimicrobial agent in the formula) is a novelty.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 There are already some commercially available formulations of mouthwashes and dentifrices containing natural substances. 11,12 Previous studies have reported the effects of natural substances on microbial growth, polysaccharides synthesis and dental biofilm formation. 13 Essential oils are complex mixtures of volatile hydrophobic substances obtained from secondary plant metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…26 . A eficácia de cremes dentais contendo antimicrobianos naturais contra biofilmes orais já foi comprovada 27 . Neste sentido, as composições das formulações analisadas apresenta potencial antibacteriano, prevenindo a contaminação por bactérias.…”
Section: Contagem De Microrganismos Viáveis Totaisunclassified